Joint replacement technology - Revell, Peter A. (Peter Allen), 1943-; ScienceDirect eBooks (Cambridge : Woodhead, 2014)
Joint replacement is a standard treatment for joint degradation and has improved the quality of life of millions of patients. For its continued success and to meet the rising expectations of patients and surgeons, it relies on collaboration between clinicians and researchers. This second edition provides a comprehensive review of the scientific and engineering developments in joint replacement technology. Part one introduces the advances in joint replacement technology, tribological considerations and experiments, and immune and regenerative responses to joint replacements. Part two.
Introduction to joint replacement technology -- Materials and techniques in joint replacement -- Biological and mechanical issues in joint replacement -- Replacing specific joints.
Print version record.
Includes bibliographical references and index.
Elsevier
Safari Books Online
Keywords: Artificial joints; MEDICAL -- Surgery -- General; Artificial joints; Electronic books